Effect of central corticotropin releasing factor on hepatic circulation in rats: the role of the CRF2 receptor in the brain. Issue 2 (11th January 2005) - Yoneda, M; Nakamura, K; Nakade, Y; Tamano, M; Kono, T; Watanobe, H; Shimada, T; Hiraishi, H; Terano, A
Abstract : Backgrounds: Corticotropin releasing factor (CRF) is distributed in the central nervous system and acts as a neurotransmitter to regulate gastric functions through vagal-muscarinic pathways. We have recently demonstrated that central CRF aggravates experimental acute liver injury in rats. In the present study, the central effect of CRF on hepatic circulation was investigated. Methods: Hepatic surface perfusion was determined by laser Doppler flowmetry in urethane anaesthetised rats. Portal pressure and portal blood flow was simultaneously monitored. CRF (0.1–4 nmol), urocortin II (a selective CRF2 receptor agonist 2.5–100 pmol), or saline vehicle was injected intracisternally, and changes in hepatic circulation were observed for 120 minutes. We examined the effects of various pretreatments with K41498, a selective CRF2 receptor antagonist, atropine, 6-hydroxydopamine, hepatic plexus denervation, or hepatic branch vagotomy, respectively. Results: Intracisternal injection of CRF (0.2–4 nmol) caused a dose dependent decrease in hepatic surface perfusion with a maximum response occurring 60 minutes post injection. Portal pressure was dose dependently elevated and portal blood flow was decreased by intracisternal CRF concurrently with the decrease in hepatic surface perfusion. These changes in hepatic circulation by intracisternal CRF were abolished by 6-hydroxydopamine and hepatic plexus denervation, but not by atropine or hepatic vagotomy. Urocortin II injected intracisternally decreased hepatic surface perfusion and elevated portal pressure at doses within the picomolar range. Intracisternal preadministration of K41498 inhibited the effect of central CRF on the hepatic circulation. Conclusion: These data suggest that CRF acts in the brain to decrease hepatic surface perfusion and elevate portal pressure through central CRF2 receptor and sympathetic-noradrenergic pathways.